Effect of heat treatment on microstructure and properties of powder immersion reaction assisted chromium carbide coatings prepared on Q235 steel. Issue 3 (15th January 2022) - Wu, Shoujun; Fu, Guo; Zhang, Bo; Chen, Yue; He, Wei; Zhang, Bin; He, Bin
Abstract: In this work, powder immersion reaction assisted (PIRAC) chromium carbide coatings prepared on Q235 steel at 800 and 900°C were heat‐treated in vacuum at 900 and 1000°C, respectively. The effects of heat treatments on the phase compositions, microhardness, and oxidation behavior in the air of the as‐prepared PIRAC chromium carbide coatings were investigated. Under further heat treatments, Cr23 C6 in the chromium carbide coatings was carburized due to the diffusion of carbon and transformed into Cr3 C2 and Cr7 C3 and subsequently, the microhardness of the coatings increased. The higher the heat treatment temperature, the higher the amount of Cr3 C2 and Cr7 C3 and the greater microhardness of the coatings. The as‐prepared and heat‐treated chromium carbide coatings experienced similar parabolic oxidation weight gains with time. Further heat treatments led to the oxidation‐induced weight gain and the parabolic oxidation rate constant decreased.